Bilobed Flap in Reconstruction of Nasal Defect - Surej Kumar L.K; Varun Menon P (Journal of Clinical Case Reports and Images, 2019)
Basal cell carcinoma (BCC) is the most common type of skin cancer, which arises from the basal layer of the epithelium. It is a slow growing tumor and has a low metastatic potential, it accounts for 70–80% of all cutaneous malignancies in the head face and neck region .Defects near nasal tip and ala of the nose are one of the most difficult site to cover in a single stage, bilobed flap is reported to be used very effectively to close the defect in these areas. This article reports a case of basal cell carcinoma involving the ala of the nose which was excised and the reconstruction was done using bilobed flap.
Keywords: Bilobed flap